2020
DOI: 10.32598/hms.26.4.3277.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Cellular Extract of Co-cultured Lactobacillus Casei on BAX and Human β-Defensin 2 Genes Expression in HT29 Cells

Abstract: Aims: Defensins are cysteine-rich antimicrobial cationic peptides and BAX is a proapoptotic gene that can cause cell death. This study aimed to investigate the effect of cellular extract of co-cultured Lactobacillus casei on the expression of BAX and human β-defensin 2 (hBD-2) genes in HT29 cells. Methods & Materials: This experimental study was conducted in the Research Center for Pharmaceutical Nanotechnology of Tabriz University of Medical Sciences in 2017. The HT29 cell line was obtained from the Paste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Further L. acidophilus induces apoptosis by increasing the mRNA expression of vivin and decreasing the mRNA expression of SMAC [42]. Lactobacillus casei signific increases the expression of the hBD-2 gene in the cancer colon cell line HT29 [43]. J al.…”
Section: Role Of Probiotics In Apoptosis Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further L. acidophilus induces apoptosis by increasing the mRNA expression of vivin and decreasing the mRNA expression of SMAC [42]. Lactobacillus casei signific increases the expression of the hBD-2 gene in the cancer colon cell line HT29 [43]. J al.…”
Section: Role Of Probiotics In Apoptosis Inductionmentioning
confidence: 99%
“…Further L. acidophilus induces apoptosis by increasing the mRNA expression of survivin and decreasing the mRNA expression of SMAC [42]. Lactobacillus casei significantly increases the expression of the hBD-2 gene in the cancer colon cell line HT29 [43]. Joo et al reported that nisin induced apoptosis and reduced proliferation in HNSCC cells by increasing intracellular calcium, inducing cell cycle arrest, and activating cation transport regulator homolog 1 (Chac1) [44].…”
Section: Role Of Probiotics In Apoptosis Inductionmentioning
confidence: 99%